Pengembangan Model Pembelajaran Pendidikan Agama Islam Dengan Pendekatan Simulasi - Eha Suhayati; Naylur Rosyid (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
This study aims to develop a learning model for Islamic religious education with a simulation approach in STKIP Banten. This research method uses research and development through 7 stages, namely research and data collection, needs analysis, development planning, expert evaluation, revision, user evaluation, development and revision. The experts involved in this study were material experts, instructional design experts, instructional media experts, while the test included one-on-one tests, small group tests and field tests. The instruments used to collect data were questionnaires and interviews. Ended with a test, an evaluation of the effectiveness of learning is carried out in the form of multiple choice tests (cognitive areas) and practice (psychomotor fields). The learning evaluation determines the competency standards that students must achieve after studying Islamic Education is 75 (seventy five). The results of this research data analysis can be concluded that the PAI learning model used is effective for students, because it can make it easier for students to understand competencies.